Предмет: Алгебра,
автор: Sofy20011972
упростить выражение 1,5 (x-2)-2(3-1,5x)при x=-0,2
Приложения:
Ответы
Автор ответа:
0
Ответ:
-9,9
Объяснение:
1,5(x-2) - 2(3-1,5x) при x=-0,2
1,5(-0,2-2) - 2(3-1,5×(-0,2)) = -0,3 - 3 - 6 - 0,6 = -3,3 - 6,6 = - 9,9
Автор ответа:
0
1,5 (x-2)-2(3-1,5x)=1,5х-3-6+3х=4,5х-9
Если х= -0,2 то 4,5х-9= 4,5* (-0,2)-9= -0,9-9=-9,9
Похожие вопросы
Предмет: Русский язык,
автор: multymely
Предмет: Қазақ тiлi,
автор: albinazhakuda
Предмет: Химия,
автор: ktcuser740919
Предмет: Химия,
автор: Akylanssj
Предмет: Математика,
автор: аля508